”Once a jolly swagman” : essays on migration honour of Olavi Koivukangas on his 60th birthday - Anttonen, Marjut (Siirtolaisuusinstituutti, 2001)
"Once a jolly swagman" is dedicated to Olavi Koivukangas on his 60th birthday. Fourteen writers have contributed to this publication. The collection of articles reflects the interdisciplinary nature of the field of migration research, a field that covers the whole world. Olavi Koivukangas has had a significant impact on this field. Olavi Koivukangas 60 vuotta / Toimituskunta Olavi Koivukangas turns 60 / The Editorial Board Turku – muuttoliiketutkimuksen keskus / Keijo Virtanen Ulkosuomalaiset verkostoituvat / Pertti Paasio Tabula gratulatoria The politicization ofKven identities in Northem Norway / Marjut Anttonen Nya Sverige – inte minst en historia om finländare / Ulf Beijbom Overview ofthe migration of Slaws from the Habsburg Monarchy to Canada – up to 1918 Irena Gantar Godina Migration and the future challenges in an integrated Europe / Elli Heikkilä Tom loyalties: Finnish immigrants in America and the Civil War in Finland / Michael G. Karni Suomalaisten Ruotsiin suuntautuneen siirtolaisuuden yhteiskunnalliset syyt 1900-luvulla / Jouni Korkiasaari Intemal migration and specialising labour markets in Finland / Olli Kultalahti Towards a reinterpretation of international migration / Imre Levai The collective behavior of early Finnish migration to America and Canada: an analysis of "American Fever" / Arnold R. Parr Lapsipakolaisuus 1900-luvulla ja suomalaiset sotalapset / Heikki Salminen Siirtolaisuus väestöllisenä resurssina - Suomi eurooppalaisessa kontekstissa / Ismo Söderling Immigrants' children and the problem of social control in the United States (early 20th century) / Adam Walaszek Contributors.